2005
DOI: 10.1002/syn.20118
|View full text |Cite
|
Sign up to set email alerts
|

Participation of dorsal raphe nucleus in the behavioral alteration observed after discontinuation of chronic diazepam administration: Possible neural circuitry involved

Abstract: Previous findings from our laboratory have demonstrated a positive correlation between the development of tolerance to diazepam (DZ) 5 mg/kg/day over 4 days, and increased hippocampal synaptic plasticity. It seems likely that a similar plastic phenomenon may occur on hippocampal formation after chronic (18 days) DZ administration. We postulate hippocampal long-term potentiation (LTP) underlying substrate to the behavioral alteration observed after chronic DZ administration. In the present study, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…This criteria was used considering previous results from our laboratory in which we showed that DZ‐treated animals that expressed less than 12% of time spent in open arms showed an increased hippocampal synaptic plasticity in vitro , hyperactivity of noradrenergic neurons in LC and increased serotonergic neuronal activity in the DRN in vivo, while animals that expressed more than 12% of time spent in open arms did not show these in vivo and in vitro changes when compared with control animals (Perez et al. , 2001, 2002; Almiron & Ramirez, 2005). On day 15 of withdrawal, animals were re‐evaluated in the PM test (RE‐EXPOSURE) and some contextual cues were changed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This criteria was used considering previous results from our laboratory in which we showed that DZ‐treated animals that expressed less than 12% of time spent in open arms showed an increased hippocampal synaptic plasticity in vitro , hyperactivity of noradrenergic neurons in LC and increased serotonergic neuronal activity in the DRN in vivo, while animals that expressed more than 12% of time spent in open arms did not show these in vivo and in vitro changes when compared with control animals (Perez et al. , 2001, 2002; Almiron & Ramirez, 2005). On day 15 of withdrawal, animals were re‐evaluated in the PM test (RE‐EXPOSURE) and some contextual cues were changed.…”
Section: Methodsmentioning
confidence: 99%
“…The increased neuronal activity of the DRN and LC projections may result in a disinhibition of the hippocampal synaptic function, thereby facilitating the plastic phenomenon within the hippocampus that likely modulates the reward circuitry, underlying the expression of the behavioral alterations observed during DZ withdrawal (Perez et al. , 2001, 2002; Almiron & Ramirez, 2005). Moreover, local changes in glutamatergic transmission in the hippocampus due to DZ administration cannot be ruled out.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous MK-801 administration impaired the development of anxiety signs during DZ withdrawal, with an increase in electrical activity been seen on 5-HT neurons of the DRN Fig. (2B) [4]. It has also been demonstrated that a single DZ administration induces a slow neuronal activity in the 5-HT neurons of the DRN [27].…”
Section: Dorsal Raphe Nucleus 5-ht Containing Neuronsmentioning
confidence: 86%
“…The HP, through its connections with structures such as the Amygdala or the medial Prefrontal Cortex, among others, is a brain structure implicated in contextual conditioning [35]. Furthermore, the anxiogenic effect promoted by DZ withdrawal was accompanied by signi icant Fos-positive immunoreactivity in telencephalic, diencephalic and mesencephalic areas related to anxiety and fear circuits in the brain [36], as well as to enhanced Locus Coeruleus and Dorsal Raphe Nucleus neuronal activity [16,37]. All these changes may contribute not only to the physical withdrawal symptoms involving autonomic function, but also to the increased HP plasticity that has been described to underlie DZ dependence and withdrawal [6,16,38].…”
Section: Discussionmentioning
confidence: 99%